The Links between Beliefs about Language Learning and Approaches to EFL Instructions of In-service EFL Teachers - Susanti, Susanti (International Journal of Transdisciplinary Knowledge, 2022)
This research reports the in-service teachers’ beliefs about language learning and their approaches to EFL (English as a Foreign Language) instructions. The study was conducted to answer the main questions: What are the common beliefs about language learning do the in-service EFL teachers have regarding the approaches to EFL instructions? and what are, in specific, the beliefs about language learning they have in the links with their teaching approaches? The data collected using survey called the Beliefs about Language Learning Inventory (BALLI) provided quantitative data and interviews were used to elicit the qualitative data. The result revealed that in-service EFL teachers share common beliefs regarding their approaches to EFL instructions, with an inconsistent links between their approaches in the importance of grammar in learning a foreign language and the beliefs of nature of language learning. As to the held beliefs there are four beliefs were reported, i.e.: Language learning aptitude, Difficulty of language learning, Nature of language learning, and Learning and communication strategies. This study is hoped to be significant for both theoretical and practical considerations for teachers in the EFL context.